Drought and Groundwater Development - Chung, Sang Yong; Kim, Gyoo-Bum; Senapathi, Venkatramanan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Drought and Groundwater Development is an important reference work in the field of groundwater science. Covering various topics related to groundwater contamination and aquifer management, this reprint makes an important contribution to the field of hydrogeology and hydrology by providing up-to-date, comprehensive, and holistic information on groundwater management during droughts. Key features:- Presents global case studies that show readers how this problem affects sites around the world.- Includes a remediation plan, problem-solving, groundwater management, water treatment techniques, and management of available groundwater resources.- Provides advanced techniques that can be applied as a methodology for solving.